Biochemical and growth-based screening for salt tolerance in aromatic aman rice at seedling stage - Parvin, Shayma; Mia, Md Abdul Baset; Israr, Md; Khan, Haider Ikbal; Ivy, Nasrin Akter (Annals of Bangladesh Agriculture, 2025)
Early screening at the seedling stage can significantly reduce the time and effort needed to develop new salt-tolerant varieties. With this objective, the Department of Crop Botany, GAU, has developed nearly 100 advanced lines of aromatic rice and evaluated them for salinity tolerance at the seedling stage. These lines were evaluated for salinity tolerance at the seedling stage under pot culture conditions, following a completely randomized design. A salinity level of 8 dSm-1 was applied, and relevant physiological and morphological data were systematically recorded. The findings revealed that in control, plant height was in between 34.17 and 56.83 cm. In contrast, under salinity, it varied from 30.17 cm and 55.00 cm. With an average of 87.47%, the relative height of seedlings ranged between 76.28% and 98.54%. The shoot elongation rate of rice seedlings in control ranged 0.38 cm day-1 to 2.24 cm day-1, while, under salinity, it varied from 0.1 cm day-1 to 2.02 cm day-1. The average shoot elongation rate for control and salinity was 1.26 and 0.53 cm day-1, respectively. The relative elongation rate ranged from 10.23% to 97.22%, averaging 43.40%. The dry weight of seedlings in control ranged from 0.35 g to 1.63 g, averaging 0.79 g, compared to 0.10 g to 1.52 g under salinity, averaging 0.54 g. Relative dry weight ranged between 22.83% to 93.26% with an average of 66.70%. Clustering and additional evaluation of the genotypes’ revealed cluster 5 containing PB38, PK37, PK50, PK51, PK52, PK85, PK86 and PK95 had higher proline accumulation (0.322 μmol g-1 FW), lower MDA (0.303 μmol g-1 FW) and a relatively higher Chl a/ Chl b ratio (2.59) under saline condition. These genotypes might be used for further hybridization program to develop new salt-tolerant rice variety. Ann. Bangladesh Agric. 28(2): 113-136